Liposomal formulations of metallophthalocyanines-nanoparticle conjugates for hypoxic photodynamic therapy and photoelectrocatalysis - Nwahara, Nnamdi Ugochinyere (Rhodes University, Faculty of Science, Department of Chemistry)
This thesis investigates new strategies to enhance the efficacy of photodynamic therapy (PDT) under hypoxic conditions using in-vitro cancer cell models. Phthalocyanines are chosen as viable photosensitizer complexes owing to the favourable absorption properties. To this end, this thesis reports on the synthesis and photophysicochemical properties of various zinc and silicon phthalocyanines (Pcs). To afford better photophysicochemical properties, the reported Pcs were conjugated to different nanoparticles (NPs) through chemisorption as well as amide bond formation to yield Pc-NP conjugates. All the studied Pcs showed relatively high triplet and singlet oxygen quantum yields corresponding to their low fluorescence quantum yields. The various mechanisms for hypoxic response include (i) Type I PDT, (ii) PDT coupled with oxygen-independent therapy and (iii) in-situ oxygen generation using catalase-mimicking nanoparticles which serve to supplement in-vitro oxygen concentrations using MPcs or MPc-NPs conjugates. The mechanisms were assessed using electrochemical, computational techniques and catalase mimicking experiments. The as-synthesised Pcs or Pc-NPs were subjected to liposomal loading before PDT studies which led to enhanced biocompatibility and aqueous dispersity. The in-vitro dark cytotoxicity tests and photodynamic therapy activities of the fabricated Pc-liposomes and Pc-NPs-liposomes on either Henrietta Lacks (HeLa) or Michigan Cancer Foundation-7 (MCF-7) breast cancer cells are presented herein. This work further showed that folic acid (FA) functionalization of liposomes could be exploited for active drug delivery and herein led to an almost 3-fold increase in drug uptake vs non-FA functionalised liposomes in accordance with folate receptor (FR) expression levels between HeLa and MCF-7 cells. The in-vitro dark cytotoxicity and photodynamic therapy of selected Pc complexes and conjugates were accessed using MCF-7 and HeLa cell lines. The various mechanisms; (i) Type I PDT, (ii) PDT coupled with oxygen -independent therapy and (iii) in-situ oxygen generation using catalase-mimicking nanoparticles were shown to adequately compensate for the otherwise attenuation of PDT activity under hypoxia.
Keywords: Liposomes; Photochemotherapy; Phthalocyanines; Photoelectrochemistry; Cancer -- Treatment